New sponge species from hydrothermal vent and cold seep sites off New Zealand - Kelly, Michelle; Rowden, Ashley A. (Zootaxa, 2019)
Three new sponge species in the demosponge families Chalinidae Gray and Suberitidae Schmidt are described from the Calypso hydrothermal vent field in the Bay of Plenty, and one species from seep sites along the Hikurangi Margin, to the east of the North Island, New Zealand. The Calypso hydrothermal vent field is dominated by the chalinid sponge Haliclona (Soestella) battershilli sp. nov., a large, cream-coloured, finely branched species, and the less common H. (Halichoclona) sonnae sp. nov., an encrusting, translucent white, cushion-shaped species. The third species, the suberitid sponge Protosuberites novaezelandiae sp. nov., forms encrustations with digitate projections. Haliclona (Halichoclona) sonnae sp. nov. and Protosuberites novaezelandiae sp. nov. represent new subgenus and genus records, respectively, for New Zealand waters. The methanotrophic suberitid sponge, Pseudosuberites thurberi sp. nov., is found at many of the cold seep sites on the Hikurangi Margin where it forms extensive, encrusting to digitate mats. The description of these species provides a basis for the future study of the ecology of sponges that are apparently endemic to vent and seep habitats off New Zealand.